(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
Mountainous territories are potential tourism areas, which are conditioned by natural resources and conditions, human intervention and existing infrastructures. As a result of investigation in the Republic of Armenia it is suggested to developed eco- and agrotourism, cognitive, scientific, business, amateur and other forms of tourism, for which a serious and effective state approach is needed.